2018
DOI: 10.1155/2018/4878503
|View full text |Cite
|
Sign up to set email alerts
|

Severe Weather Events over Southeastern Brazil during the 2016 Dry Season

Abstract: Southeastern Brazil is the most populated and economically developed region of this country. Its climate consists of two distinct seasons: the dry season, extending from April to September, the precipitation is significantly reduced in comparison to that of the wet season, which extends from October to March. However, during nine days of the 2016 dry season, successive convective systems were associated with atypical precipitation events, tornadoes and at least one microburst over the southern part of this reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…230 The MJO impacts are particularly important for extreme precipitation events over SA. 220,221,224,235 Carvalho et al 220 showed that intense SACZ events persisting for more than 3 days are associated with the active MJO. Jones et al 221 observed a higher frequency of extreme precipitation events globally.…”
Section: The Madden-julian Oscillationmentioning
confidence: 99%
“…230 The MJO impacts are particularly important for extreme precipitation events over SA. 220,221,224,235 Carvalho et al 220 showed that intense SACZ events persisting for more than 3 days are associated with the active MJO. Jones et al 221 observed a higher frequency of extreme precipitation events globally.…”
Section: The Madden-julian Oscillationmentioning
confidence: 99%
“…The quarantine beginning coincided with the dry season beginning at São Paulo, presenting a decline in temperature compared to the early months of 2020. The most significant feature of the São Paulo dry season (April to November), the wet season counterpart ( Vera et al, 2006 ), is the non-significative precipitation amount, caused by weak isolated events, and long periods with no precipitation occurring in between ( Rehbein et al, 2018 ), and the very low relative humidity during the daytime (climate reports from the Climate Group of Studies - GrEC/USP, http://www.grec.iag.usp.br ). Also, a general decreasing in temperature occurs according to the austral winter and presenting drops in temperature, associated to the synoptic systems crossing São Paulo and generally are not able to organize convection (GrEC/USP, http://www.grec.iag.usp.br ) or even sea breezes that eventually reaches the interior of São Paulo ( Freitas et al, 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…The quarantine beginning coincided with the dry season beginning at São Paulo, presenting a decline in temperature compared to the early months of 2020. The most significant feature of the São Paulo dry season (though April to November), the wet season counterpart (Vera et al 2006), is the non-significative precipitation amount, caused by weak isolated events, and long periods with no precipitation occurring in between (Rehbein et al 2018), and the very low relative humidity during the daytime (climate reports from the Climate Group of Studies - GrEC/USP, http://www.grec.iag.usp.br). Also, a general decreasing in temperature occurs according to the austral winter and presenting drops in temperature, associated to the synoptic systems crossing São Paulo and generally are not able to organize convection (GrEC/USP, http://www.grec.iag.usp.br) or even sea breezes that eventually reaches the interior of São Paulo (Freitas et al 2007).…”
Section: Methodsmentioning
confidence: 99%